Social media marketing strategy to increase brand awareness of local fashion brands - Khairunnisa, Putri Khansa; Juliadi, Rismi (Faculty of Communication Sciences Universitas Padjadjaran, 2023)
Russ & Co. is a local fashion brand from Bandung known as Paris Van Java. The fashion industries in Bandung City have been growing for three decades. The company endeavors to maintain consistent and integrated marketing communications to stay competitive. This research analyzes Russ & Co.’s social media marketing strategy as a local fashion brand during the COVID-19 pandemic. This research uses a descriptive qualitative method, data collection through in-depth interviews with four informants, data source triangulation to strengthen the research findings, and data analysis technique using qualitative data analysis. The concept of social media marketing from Tuten & Solomon is utilized. The findings indicate that Russ & Co. utilizes social media marketing to increase brand awareness amidst the COVID-19 pandemic. Instagram and TikTok are the optimal social media platforms to execute the marketing strategy. The Instagram social media strategies comprise implementing giveaways, ads, hashtags, influencer partnerships, and utilizing various platform features. On the other hand, the TikTok strategy is to create concise fashion videos imbued with humor. The findings of this study reveal the success of Russ & Co.’s social media marketing, evident through the increase in social media followers and being recognized as the top men’s clothing brand on Shopee Mall Indonesia.